Educational migration from the Republic of Buryatia: factors, scale and directions - G. N. Ochirova (Вестник университета, 2021)
The article considers the problem of educational migration of the population from the Republic of Buryatia. The paper presents the preliminary results of the author's sociological research, within the framework of which an anonymous survey of high school students in Buryatia and an expert survey of directors of general education institutions in Buryatia were conducted. The results of the study indicate a high educational migration potential among Buryat school graduates, for whom the presence of the specialty / field of study, the quality of education and the availability of budget places are significant choosing an educational institution. The study also analysed secondary data from the Ministry of Education and Science of the Republic of Buryatia, obtained at an official request, and statistical data from the Territorial Body of the Federal State Statistics Service for the Republic of Buryatia, which made it possible to determine the scale and direction of educational migration from the Republic.